Genetic Structure in Populations of Euterpe precatoria Mart. in the Brazilian Amazon - Ramos, Santiago Linorio Ferreyra; Dequigiovanni, Gabriel; Lopes, Maria Teresa Gomes; Aguiar, Ananda Virginia de; Lopes, Ricardo; Veasey, Elizabeth Ann; Macêdo, Jeferson Luis Vasconcelos de; Alves-Pereira, Alessandro; Fraxe, Therezinha de Jesus Pinto; Wrege, Marcos Silveira; Garcia, José Nivaldo (Frontiers in Ecology and Evolution, 2021)
Euterpe precatoria is a palm tree belonging to the Arecaceae family, occurring in Western and Central Brazilian Amazonia. Its fruit, which is very appreciated in the Amazon region, produces pulp for wine that is consumed in fresh form. Its production is carried out almost exclusively by extractive farmers. Therefore, it is necessary to establish adequate strategies to sustain this genetic resource. To do this, we need to know more about its diversity and genetic structure in natural populations. Consequently, this study aimed to evaluate the influence of geographic distance on genetic structure in the main extractive populations of E. precatoria in the Brazilian Amazon. Therefore, leaves from 377 plants were collected in 19 populations located in 16 municipalities in the State of Amazonas and three in the State of Rondônia. Twelve microsatellite loci were amplified by polymerase chain reaction and subsequently genotyped by capillary electrophoresis. The parameters of diversity and genetic structure among populations were estimated. The average number of alleles per locus in the populations was 5.97. The observed heterozygosity means (HO) were higher than expected (HE) at the population level (HO = 0.72, HE = 0.66). The inbreeding coefficient (f = -0.100) showed negative values. The FST value (0.1820) and the AMOVA results (17.961) showed population structure. The populations were clustered into three groups (K = 3) in Bayesian analysis. The Discriminant Analysis of Principal Components (DAPC) confirmed eight clusters, but the populations were close to those identified by the Bayesian analysis. Genetic diversity indices indicate high diversity and the possibility that reproductive strategy in the species stems from allogamy, while the genetic structure indicates the most likely grouping at the level of hydrographic basins.